Valores antropométricos de referencia para la clasificación del talento en la lucha - Sancesario Perez, L. A.; Rosales Carrazana, A. R. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2006)
We studied 64 Free Style Wrestling athletes of 13-14 year old, of 8 corporals weight divisions, of 5 Cuban Oriental provinces. Beginning from anthropometrics measurement, and after be obtained the underlying morphological patrons on the object of study athletes and their importance order for talents selection process, it proposes values to classify the athletes, according to variable, in Talent 1 or Talent 2.